A case of severe psoriatic erythroderma with COVID-19. (17th February 2022) - Ghalamkarpour, Fariba; Pourani, Mohammad Reza; Abdollahimajd, Fahimeh; Zargari, Omid
Abstract: COVID-19 caused by the SARS-CoV-2, became pandemic very quickly. Management of severe dermatologic disorders in patients who require systemic immunosuppressive treatment is a major concern in COVID-19 pandemic era. Here, we report a 45-year-old homeless addicted male with second flare of psoriatic erythroderma and positive PCR test for COVID 19. His first attack occurred two months earlier, when he was screened for SARS-CoV-2 before admission which all evaluations showed nagative results. The patient was treated and relatively controlled with cyclosporine and therefore he was discharged. During this interval, he not only discontinued his medication, but also became SARS-CoV-2 positive. It seems that both factors participated in flare of his erythroderma.